Privatization: Do prices rise or fall? Mixed duopoly with vertical differentiation - Arteaga García, Julio César; Cárdenas Rodríguez, Oscar J.; Flores Curiel, Daniel (Estudios Económicos de El Colegio de México, 2004)
In this paper, we use a duopoly model with vertical (quality) product differentiation to determine whether privatization of a public firm leads to higher or lower prices than those prevailing in a mixed duopoly. We show that privatization can move prices on either direction.